Effects of extrusion conditions on the physicochemical properties of soy protein/gluten composite - Wu, Min; Sun, Yang; Bi, Chonghao; Ji, Fang; Li, Borui; Xing, Junjie (International Journal of Agricultural and Biological Engineering, 2018)
Soybean protein-gluten blend was extruded using a co-rotating twin-screw extruder. Effects of different extrusion conditions on the textural properties of extrudates were analyzed by central composite design through the evaluation of texturization index, water holding capacity, and hardness of extruded protein products. Extrusion process variables including feed moisture content (40%-60%), screw speed (12-20 Hz), extrusion temperature (120°C-180°C), and gluten content (16%-32%) were studied by the nonlinear regression equations analysis. The extrusion process was also optimized using response surface methodology (RSM). The influence of moisture content on the hardness of extrudate was the most significant. The optimized results, including feed moisture content, extrusion temperature, screw speed and gluten content were 49.18%-50.15%, 155.24°C-159.86°C, 16.41-16.73 Hz, 20.00%-20.03%, respectively. The microstructures of TISP products were analyzed by scanning electron microscopy (SEM) and the changes of protein molecules before and after extrusion were also analyzed by SDS-PAGE electrophoresis. Keywords: soybean protein, gluten, extrusion, response surface methodology (RSM), SDS-PAGE electrophoresis, Microstructural properties DOI: 10.25165/j.ijabe.20181104.4162 Citation: Wu M, Sun Y, Bi C H, Ji F, Li B R, Xing J J. Effects of extrusion conditions on the physicochemical properties of soy protein/gluten composite. Int J Agric & Biol Eng, 2018; 11(4): 230-237.